KAJIAN APRESIATIF DAN KRITIS TERHADAP PUISI ‘AKU’ KARYA CHAIRIL ANWAR DALAM PERSPEKTIF EKSPRESI INDIVIDUALISME - Adzkia Rizkianisa Awira Siregar; Intan Maharani Daulay; Lorenza Medolu Waruwu; Mika Debora Hutasoit; Taestin Glorya Gift Siboro; Atika Wasilah Sipayung (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines chairil anwar's poem "aku" appreciatively and critically from the perspective of individualistic expression. This study is motivated by the strong representation of individualism in the poem, which is displayed through the freedom, courage, and spirit of resistance of the lyricist character against social pressures and the limitations of life. The study aims to understand the aesthetic value and power of linguistic expression in the poem and to examine how the idea of individualism is represented through the language structure and attitudes of the lyricist character. The method used is descriptive qualitative research with a library research approach. Primary data consists of the text of the poem "aku," while secondary data are obtained from scientific journals, books, research articles, and various references related to literary appreciation, literary criticism, individualism, and expressive approaches. Data collection techniques are carried out through documentary studies to obtain and understand data related to the research object in greater depth. Data analysis is carried out by identifying the elements of the poem, grouping relevant data, interpreting the forms of individualism that emerge, and then examining them appreciatively and critically. The results of this study indicate that the expression of individualism in the poem "aku" (i) is constructed through the dominance of the pronoun "aku," the use of aggressive metaphors, violent imagery, and the lyrical character's courageous and defiant attitude. This poem possesses both aesthetic and profound philosophical value regarding the relationship between humans and themselves, society, and life. Thus, the poem "aku" (i) is a powerful representation of individualism in modern indonesian literature, embodying the spirit of freedom, existence, and resistance.